Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.trsl.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Using GWAS to identify novel therapeutic targets for osteoporosis

Abstract: Osteoporosis is a common, increasingly prevalent, global health burden characterized by low bone mineral density (BMD) and increased risk of fracture. Despite its significant impact on human health, there is currently a lack of highly effective treatments free of side effects for osteoporosis. Therefore, a major goal in the field is to identify new drug targets. Genetic discovery has been shown to be effective in the unbiased identification of novel drug targets and genome-wide association studies (GWASs) have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 117 publications
0
36
0
Order By: Relevance
“…Although osteoporosis is a multifactorial disease influenced by both environmental and genetic variation, fracture-related traits, such as BMD, are influenced, in large part, by genetics (h 2 >0.5) 35 . Over the last decade large-scale genome wide association studies (GWASs) have begun to dissect the genetics basis of bone traits with a primary focus on BMD 6, 7 . These studies have been tremendously successful, identifying over 1100 independent BMD associations 810 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although osteoporosis is a multifactorial disease influenced by both environmental and genetic variation, fracture-related traits, such as BMD, are influenced, in large part, by genetics (h 2 >0.5) 35 . Over the last decade large-scale genome wide association studies (GWASs) have begun to dissect the genetics basis of bone traits with a primary focus on BMD 6, 7 . These studies have been tremendously successful, identifying over 1100 independent BMD associations 810 .…”
Section: Introductionmentioning
confidence: 99%
“…These studies have been tremendously successful, identifying over 1100 independent BMD associations 810 . However, despite the wealth of genetic signals, the genes and mechanisms through which these associations impact bone remain largely unknown 6, 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In China, the prevalence rate of osteoporosis in older adults was estimated to be 15.7%, and it will increase rapidly with the increasing age of the total population [6]. Despite the significant impact on human health, there is still a lack of highly effective osteoporosis treatments that are free of negative side effects [7]. Hence, identification of additional therapeutic molecular targets for effective and efficient prevention and treatment of osteoporosis are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Co-expression networks are modular, and each module represents a group of co-expressed genes. These modules tend to contain genes involved in similar biological processes [7]. Hence, under WGCNA, we explored the functional relevance of the identified novel genes to other known putative osteoporosis genes in order to explore the potential functional mechanisms of the identified novel genes.…”
Section: Introductionmentioning
confidence: 99%
“…BMD has a strong heritable component, with an estimated heritability of 50% to 85% (5)(6)(7)(8). In recent years, genome-wide association studies identified .100 genetic loci associated with BMD (9,10). For instance, Estrada et al (11) identified 56 BMD-associated loci through a large scale genome-wide meta-analysis.…”
mentioning
confidence: 99%